Vertical distribution of water vapor using satellite sounding methods with new aircraft data validation - McNoldy, Brian D., author; Vonder Haar, Thomas, advisor; Stephens, Graeme, committee member; She, Chiao-Yao, committee member (Colorado State University. Libraries, 2001)
The importance of water vapor in Earth's climate system is undisputedly immense. Its meteorological impacts range from radiative transfer to the hydrologic cycle, on scales ranging from local to planetary. It affects military operations, commercial flights, and private industry. However, global measurements of water vapor can currently only be obtained from satellites, since ground stations are sparse and ocean stations are nearly non-existent. Unfortunately, the satellites cannot directly measure water vapor; instead, they detect radiation at discrete frequencies. The signals originate from different altitudes in the atmosphere, providing vertical resolution. A complex mathematical inversion is necessary to retrieve the desired quantity (water vapor) from the measured quantity (brightness temperatures). Both the satellite calibration and the retrieval algorithm contribute to errors in the retrieved parameters. The focus here is on the validation of a satellite-based retrieval using in-situ measurements of water vapor made by commercial aircraft. The Aircraft Communications Addressing and Reporting System (ACARS) routinely records a plethora of meteorological parameters, including temperature, pressure, wind velocities, and turbulence. The new Water Vapor Sensing System (WVSS) added water vapor mixing ratio and dewpoint to the array of parameters. These measurements will be compared to the humidity measurements retrieved from the satellite-based TIROS Operational Vertical Sounder (TOVS) High-resolution Infrared Radiation Sounder (HIRS) radiances over the continental United States. This study shows that the water vapor retrieval algorithm is approximately 20% too dry through most of the atmosphere when compared to aircraft measurements of the same parameter.
Keywords: Water vapor, Atmospheric -- Remote sensing -- Evaluation; Water vapor, Atmospheric -- Measurement; Meteorological satellites -- Evaluation